Is there a distinction between malaria treatment and intermittent preventive treatment? Insights from a cross-sectional study of anti-malarial drug use among Ugandan pregnant women - Odongo, Charles O; Bisaso, Kuteesa R; Kitutu, Freddy; Obua, Celestino; Byamugisha, Josaphat (Malaria Journal, 2022)
Background: In Uganda, treatment of clinical malaria and intermittent preventive treatment with sulphadoxine pyrimethamine (SP) are common during pregnancy. As a result, both formal and informal reports from antenatal sources suggest possible misuse of SP for malaria treatment among pregnant women. The objective of this study was to investigate anti-malarial drug use patterns among women who had recently suffered malaria illness before and during pregnancy. Methods: A cross-sectional study in which a structured questionnaire (interviewer-administered) was used to collect data from pregnant women attending an urban antenatal clinic. Details of medicines used to treat malaria episodes suffered before and during pregnancy were captured. A first order Markov probability model was used to estimate probabilities of transitioning between treatment choices made before and during pregnancy. Logistic regression was used to explore whether demographic and obstetric characteristics were associated with transition patterns. Results: Seven hundred women were interviewed among whom 428 had suffered malaria in both instances. Three hundred thirty of these could recall the medicines used in both instances. Women who used ACT/QNN (correct choice) before pregnancy had higher probabilities of transitioning to SP than staying on ACT/QNN during pregnancy (0.463 versus 0.451). Access of medicines from private outlets (clinics and pharmacies) were more than nine times predictive of receiving correct medicines (p=0.035 and p=0.039 respectively). Access of medicines from clinics was 5.9 times protective against receiving SP for malaria treatment (p=0.033). Among those who used SP before pregnancy, there was a 0.75 probability of staying on it during pregnancy. None of the factors explored could explain this observation. Conclusion: Use of SP for malaria treatment is common during pregnancy. This may be contributing to adverse pregnancy outcomes. Antenatal care providers should endeavor to emphasize the distinction between treatment and prevention of malaria during pregnancy.
Keywords: Malaria treatment; Intermittent preventive treatment; Sulphadoxine-pyrimethamine; Pregnant women; Uganda